2012
DOI: 10.1177/0018720812462388
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Approach to Shared Knowledge

Abstract: Although we do not examine team performance directly, we demonstrate that shared knowledge is related to the technical design and thus provide a foundation for improving design products by incorporating the knowledge and thoughts of the engineering design team into the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This approach should be distinguished from, and is complementary to, recent structural or network approaches to shared team knowledge (e.g. Avnet and Weigel 2013;Espinosa and Clark 2014). We focus on real-time team communication, while the latter approaches use surveys to capture team knowledge network structures.…”
Section: Social Network Analysismentioning
confidence: 99%
“…This approach should be distinguished from, and is complementary to, recent structural or network approaches to shared team knowledge (e.g. Avnet and Weigel 2013;Espinosa and Clark 2014). We focus on real-time team communication, while the latter approaches use surveys to capture team knowledge network structures.…”
Section: Social Network Analysismentioning
confidence: 99%
“…Difficulties associated with emergent state measurement have driven the development of innovative, non-obtrusive measures such as social network analysis (SNA), sociometric badges, vocal recognition, content analysis, and archival data analysis. For example, SNA has recently been used to measure SMM (Avnet & Weigel, 2013) and cohesion (Wise, 2014), while content analytic approaches have been used to measure cohesion (Gonzales, Hancock, & Pennebaker, 2010) and collective cognition (Clariana & Wallace, 2007).…”
Section: Issues In Emergent State Measurementmentioning
confidence: 99%
“…Resick and colleagues (2010) showed that a network approach to modeling team cognition was superior for predicting performance than were other metrics of team cognition. In our review, we noted a recent uptick in articles using network analyses to study emergent states such as team trust (Lusher, Kremer, & Robins, 2014), cohesion (Tirado et al, 2012; Wise, 2014; Zaheer & Soda, 2009), affective climate (Yuan et al, 2014), team mental models (Avnet & Weigel, 2013; Dionne, Sayama, Hao, & Bush, 2010), TMS (Comu et al, 2013; Espinosa & Clark, 2014), and situational awareness (Sorensen & Stanton, 2011). Network operationalizations are most relevant when a construct may have meaningful intradyadic variance, such that the felt presence of a given emergent state may differ from dyad to dyad.…”
Section: Issues In Emergent State Measurementmentioning
confidence: 99%
“…For example, Bucciarelli (1994), notes that professional disciplines function as separate “cultures”, which could lead one to conclude that multidisciplinary design teams are especially likely to be subject to cyclic preferences. However, recent data indicate that members of multidisciplinary design teams do indeed construct shared mental models (Avnet 2015, 2016; Avnet and Weigel 2013) suggesting that culture, as defined by Bucciarelli, does not preclude shared cognitive representations (see also, Romney et al 1986, 1996). Future work should therefore focus on determining the situations under which group members’ mental models diverge in a manner that allows for cyclic preferences to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these constraints are often natural, not artificial. Several bodies of scholarly literature have independently concluded that structured mental constraints, or “mental models”, are often held in common by members of a design team (e.g., Ahamed et al 2016; Anderson 1995; Avnet and Weigel 2013; Langan-Fox et al 2000, 2004). Structured mental models are a result of deep domain expertise that are strongly shaped by empirical regularities (e.g., Bang et al 2007; Reyna and Lloyd 2006; Romney et al 1996, 1986).…”
Section: Introductionmentioning
confidence: 99%